2004
DOI: 10.1897/03-365
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of accumulation of micropollutants between indigenous and transplanted zebra mussels (Dreissena polymorpha)

Abstract: Zebra mussels (Dreissena polymorpha) were exposed at 12 canals and lakes situated in Flanders (Belgium), in cages for six weeks during the summer of 2002. Accumulation of polychlorinated biphenyls (PCBs), polybrominated diphenyl ethers (PBDEs), hexachlorobenzene, and trace metals were measured in the transplanted mussels and levels compared to levels in indigenous mussels. Additionally, zebra mussels were exposed at a small lake in the vicinity of Antwerp (Belgium), and accumulation of contaminants was followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 49 publications
2
40
0
Order By: Relevance
“…This can be explained by the fact that, like most aquatic organisms, M. iridescens can efficiently, at least to a certain extent, regulate uptake and/or excretion of essential metals through homeostatic mechanisms over a wide range of ambient exposure levels, while for the non-essential metals, there appeared to be no, or only a weak, mechanism to regulate or limit uptake or excretion (Voets et al, 2009) tial trace metals with some form of homeostatic control. In this respect, our results are completely in accordance with the findings of other researchers (Bervoets et al, 2004;Bonneris et al, 2005), who also reported that bioaccumulated Cd concentrations were more responsive to the spatial gradients than were those of bioaccumulated Zn, even though the ambient [M] max /[M] min ratios in exposure conditions were less for Cd than for Zn. In a biomonitoring context, M. iridescens would thus be more responsive to the external Cd and Pb exposure gradients than to the Cu and Zn exposure gradients.…”
Section: Bioaccumulation Differences Between Essential and Non-essentsupporting
confidence: 93%
“…This can be explained by the fact that, like most aquatic organisms, M. iridescens can efficiently, at least to a certain extent, regulate uptake and/or excretion of essential metals through homeostatic mechanisms over a wide range of ambient exposure levels, while for the non-essential metals, there appeared to be no, or only a weak, mechanism to regulate or limit uptake or excretion (Voets et al, 2009) tial trace metals with some form of homeostatic control. In this respect, our results are completely in accordance with the findings of other researchers (Bervoets et al, 2004;Bonneris et al, 2005), who also reported that bioaccumulated Cd concentrations were more responsive to the spatial gradients than were those of bioaccumulated Zn, even though the ambient [M] max /[M] min ratios in exposure conditions were less for Cd than for Zn. In a biomonitoring context, M. iridescens would thus be more responsive to the external Cd and Pb exposure gradients than to the Cu and Zn exposure gradients.…”
Section: Bioaccumulation Differences Between Essential and Non-essentsupporting
confidence: 93%
“…In this study, Mytilus galloprovincialis (Lamark 1819), a Mediterranean mussel, has been used as a model since this organism is a filter feeder and effective 'bioaccumulator' organism, thus providing a reliable indicator of organic pollutants in water. [12] Although several synthetic congeners may exist, only a small number of PBDEs can be found in technical mixtures; [13] of these synthetic PBDE congeners, BDE-28, BDE-47, BDE-99, BDE-100, BDE-153 and BDE-154 are of primary interest to EC (Decision no. 2455/2001/EC).…”
Section: Introductionmentioning
confidence: 99%
“…Klerks and Weis (1987) indicated that the responses of animals to metal pollution is the result of either physiological acclimatization, representing a degree of tolerance obtained during a relatively short-time exposure, or adaptation, representing the genetically based resistance obtained by whole lifetime exposure. Specifically, recent studies have demonstrated that populations exposed to metals show a better tolerance to metal contaminations than populations which have never experienced selected contaminants (Bervoets et al 2004;Lapanje et al 2008;Ross et al 2002). Similar local adaptation was also highlighted in populations experiencing pathogenic organisms, such as toxic algae (Hégaret and Wikfors 2005) or trematode parasite (Bryan-Walker et al 2007) compared to populations without prior exposures.…”
Section: Introductionmentioning
confidence: 77%
“…Within the last decade, numerous studies have investigated the potential role of environmental history on tolerance to stress in several organisms such as plant (Eränen 2006), bryozoan (Piola and Johnston 2006), insect (Shirley and Sibly 1999), fish (Nacci et al 2002;Ownby et al 2002), crustacean (Ross et al 2002;Lapanje et al 2008), and mollusk (Bervoets et al 2004). In the present study, clams from a Cd-enriched site (Andernos) showed a stronger Cd accumulation in relation to a higher MT concentration and a faster transfer of Cd from gills to visceral mass than in clams from Arguin (non-contaminated site).…”
Section: Resultsmentioning
confidence: 99%